The Power of Precision: Why Your Research Focus Should be SMART? - Adeoye, Moses Adeleke; Adong, Christine (Universitas Pendidikan Ganesha, 2023)
Having a SMART research focus is essential for researchers to achieve the desired results. By being specific, measurable, achievable, relevant, and time-bound, researchers can improve the effectiveness and efficiency of their research. This study aims to explore the importance of having a SMART (Specific, Measurable, Achievable, Relevant, and Time-bound) research focus. This study used a descriptive-analytical approach by collecting data through literature review and analysis of existing research. The collected data is analyzed qualitatively by reading, understanding, and synthesizing relevant information. The results of this study show that a SMART research focus can increase research productivity, improve decision-making processes, and increase the chances of obtaining meaningful results. In conclusion, by adopting the SMART framework researchers can maximize the effectiveness and efficiency of research results significantly. Thus, this study provides a better understanding of the importance of having a SMART research focus and has implications for more effective and efficient research in the future.